Prove conjugation law for Exp(z) using only Exp(x + y) = Exp(x)Exp(y)

Starting with just the property $ E(x + y) = E(x)E(y)$ , one can prove quite a lot of the main properties of the exponential function on real numbers. For example, $ E(0) = 1$ , and $ E'(X) = E(X)$ , and $ E(nx) = E(x)^n$ all follow from a straight-forward application of definitions.

To move this in to complex analysis and Euler’s formula, it seems to me that the key property that needs to be proved is $ E(\overline{z})$ = $ \overline{E(z)}$ .

Is there a nice way to prove this that is in the spirit of this particular line of reasoning?

Edit: For example, Chapter 8 of Baby Rudin follows this reasoning, but resorts to the definition $ E(x) = \Sigma_{n\ge0}(\frac{z^n}{n!})$ to prove the conjugation property.